Identification of distribution changes of leachate in a landfill. Issue 1 (January 2021) - Musa, M D T; Elisabeth, J C; Jamidun,; Labania, H M D
Abstract: The distribution of leachate in the Kawatuna landfill, Palu City, which is still implementing the Open Damping system, has been researched in 2011 where it was detected up to a depth of 7 meters and led to reservoir of leachate. The Landfill Control system has been implemented, but the leachate pipe was not functioning, and part of the storage pool was damaged during the earthquake on September 28, 2018, so that leachate is scattered everywhere. This study aims to determine changes in the distribution of leachate used geoelectric-resistivity method with Wenner-Schlumberger configuration. Data were collected at 3 points within the landfill site and 1 point outside the location, with a length of 48 meters each and processed using EarthImager 2D software. From the research results, it is obtained that the resistivity value of leachate is 1–9.7 ohmmeter. Based on the cross-sectional resistivity analysis, leachate was spread to a depth of 9.7 m, which indicates an increase depth of 2.7 m and the distribution direction was not leading to reservoirs of leachate